PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN PRODUK KREDITMU - Pradana, Radiktya Dagda (PRIMA EKONOMIKA, 2021)
The purpose of this study is to determine the effect of integrated marketing communication on consumer decisions using your credit products. The research method used is descriptive research method followed by explanatory research method. Determination of the sample is done by cluster technique with a sample number of 120 respondents. The data was analyzed by structural equation modeling (SEM) using the Amos program. The results of the analysis show that integrated marketing communication has a positive and significant influence on your credit usage decisions. This study also found that advertising, sales promotion and direct marketing partially gave a significant influence on problem recognition, research information, evaluation alternatives and purchase decisions. Whereas public relations influence problem recognition, evaluation alternatives and purchase decisions, but does not have a significant influence on research information. Then personal selling has an effect on problem recognition, research information, and purchase decision, but does not have a significant effect on evaluation alternatives. Keywords: Integrated Marketing Communication, Consumer Decisions, Credit usage